Egg mortality of Lake Geneva charr (Salvelinus alpinus L.) contaminated by PCB and DDT derivatives - Monod, Gilles (HAL CCSD, 1985)
Egg mortality of Lake Geneva charr (Salvelinus alpinus L.) contaminated by PCB and DDT derivatives